P4.43 Socio-economic status of men engaging in age disparate sex: a secondary analysis of nationally representative data in south africa. (8th July 2017) - George, Gavin; Beckett, Sean; Maughan-Brown, Brendan; Evans, Meredith
Abstract : Introduction: Studies have highlighted the increased risk in contracting HIV for young women who engage in age disparate sexual partnerships. However, there is a dearth of evidence about the socioeconomic profile of men who engage in these types of sexual partnerships. This study focuses on men who engage in age disparate sex and specifically whether there are socioeconomic-status (SES) asymmetries between those who engage in age disparate sex compared to those who do not engage in age disparate sex. Methods: The data for this study comes from the third National HIV communication Survey (NCS) of South Africa conducted in 2012. The sample consists of 4065 randomly selected men between the ages of 16 and 55 years. Respondents were interviewed by means of a structured questionnaire. Men were classified according to the types of sexual partnerships they had engaged in during the previous 12 months. Multiple logistic regression models were used to assess the association between SES and sexual partnership type, controlling for potential confounders. Results: Sixty percent of men had been involved in only age similar partnerships, 31% in at least one age disparate partnership (partner is 5 to 9 years younger) and 10% in relationships where the female partner is 9 years or more years younger. The results indicate that household wealth is not significantly related to the likelihood of men engaging in age disparate sex or intergenerational sex. Interestingly, experiencing deprivation in informal urban areas increases men's likelihood of engaging in age disparate sex (AOR: 1.3, p<0.05). Conclusion: The results reveal that it is poorer men in informal urban settlements who are engaging in age disparate sex. Literature suggests that young women primarily engage in transactional sex with older men to support their basic needs. However, these data do not support this hypothesis and future research must identify the full range of factors fueling age disparate relationships.